Performance of HPV E6/E7 mRNA assay as primary screening test: Results from the NTCC2 trial. Issue 7 (7th June 2022) - Giorgi Rossi, Paolo; Ronco, Guglielmo; Mancuso, Pamela; Carozzi, Francesca; Allia, Elena; Bisanzi, Simonetta; Gillio‐Tos, Anna; De Marco, Laura; Rizzolo, Raffaella; Gustinucci, Daniela; Del Mistro, Annarosa; Frayle, Helena; et al.
Abstract: As the primary screening test, E6/E7 mRNA has shown similar sensitivity for CIN3+ and lower positivity rate than the HPV DNA test. Nevertheless, the overall mRNA positivity is too high for immediate colposcopy, making a triage test necessary. The aim was to estimate the mRNA performance as a primary test with different triage strategies. All HPV DNA‐positives were tested for mRNA, cytology and p16/ki67. A sample of HPV DNA‐negatives was also tested for mRNA to estimate test specificity. We included all CIN3+ histologically diagnosed within 24 months since recruitment. Of the 41 127 participants, 7.7% were HPV DNA‐positive, of which 66.4% were mRNA‐positive. Among the HPV DNA‐negatives, 10/1108 (0.9%) were mRNA‐positive. Overall, 97 CIN3+ were found. If mRNA was used as the primary test, it would miss about 3% of all CIN3+ with a 22% reduction of positivity compared with HPV DNA. The weighted specificity estimate for <CIN2 was 94.5% (95% CI = 93.9%‐94.9%) and sensitivity for CIN3+ was 96.9% (95% CI = 91.3%‐99.1%). If all the weighted estimated 6.0% mRNA‐positive women had been referred to colposcopy, PPV for CIN3+ would have been 4.2%. Cytology or p16/ki67 triage would decrease immediate referral to 1.7% and 2.0%, increasing PPV to 11.2% and 11.7%, respectively; total colposcopy referral would be 4.0% and 3.9%, respectively. As the primary screening test, the mRNA assay showed a positivity rate lower than that of HPV DNA, with a small number of CIN3+ missed. Triage with cytology or p16/ki67 would only marginally decrease overall colposcopy referral. Abstract : What's new? Human papillomavirus (HPV) DNA‐based assays are now widely recommended for cervical cancer screening, but they lack specificity. As a primary screening test, E6/E7 mRNA testing has shown a similar sensitivity for CIN3+ but a lower positivity rate than HPV DNA testing. This trial study shows that primary E6/E7 mRNA screening would miss about 3% of CIN3+ cases. Overall positivity would be 22% lower than that of HPV DNA. Triage with cytology or p16/ki67 dual staining would only marginally decrease overall colposcopy referral if retesting of E6/E7 mRNA‐positive/triage‐negative women was performed with HPV DNA assays after 12 months.